Polyvinyl alcohol-polyethylene glycol/glycerin hydrogel enhanced physicochemical characteristics: statistical composition - Jafri, Nur Huda Syazwani; Jimat, Dzun Noraini; Wan Nawawi, Wan Mohd Fazli; Ahmad Nor, Yusilawati (IIUM Press, 2025)
Polyvinyl alcohol (PVA) hydrogels are widely recognized for their potential in biomedical applications, particularly as wound dressings, due to their biocompatibility and water retention properties. However, their performance can be enhanced through modifications in composition and cross linking with other polymers. This study aims to improve the properties of PVA hydrogels by incorporating polyethylene glycol (PEG) and glycerin through the freeze-thaw method. Central composite design (CCD) and response surface methodology (RSM) were employed to investigate the effect of PEG and glycerin concentrations on moisture retention capability (MRC). The optimized composition, with 6% (w/v) PEG and 4% (w/v) glycerin, achieved the highest MRC at 46.82 ± 0.54%. The hydrogel exhibited a swelling capacity of 143.24 ± 1.66%, a gel fraction of 58.06 ± 1.65%, and a porosity of 42.17 ± 0.94%. Field-emission scanning electron microscopy (FESEM) confirmed the surface features and porosity, while Fourier transform infrared (FTIR) spectroscopy analysis verified the cross-linking within the PVA-PEG matrix with glycerin. These findings highlight the potential of the hydrogel for wound dressings due to its favorable properties